Agents with vasodilator properties in acute heart failure: how to design successful trials. (4th June 2015) - Mebazaa, Alexandre; Longrois, Dan; Metra, Marco; Mueller, Christian; Richards, Arthur Mark; Roessig, Lothar; Seronde, Marie France; Sato, Naoki; Stockbridge, Norman L.; Gattis Stough, Wendy; Alonso, Angeles; Cody, Robert J.; et al.
Abstract Agents with vasodilator properties (AVDs) are frequently used in the treatment of acute heart failure (AHF). AVDs rapidly reduce preload and afterload, improve left ventricle to aorta and right ventricle to pulmonary artery coupling, and may improve symptoms. Early biomarker changes after AVD administration have suggested potentially beneficial effects on cardiac stretch, vascular tone, and renal function. AVDs that reduce haemodynamic congestion without causing hypoperfusion might be effective in preventing worsening organ dysfunction. Existing AVDs have been associated with different results on outcomes in randomized clinical trials, and observational studies have suggested that AVDs may be associated with a clinical outcome benefit. Lessons have been learned from past AVD trials in AHF regarding preventing hypotension, selecting the optimal endpoint, refining dyspnoea measurements, and achieving early randomization and treatment initiation. These lessons have been applied to the design of ongoing pivotal clinical trials, which aim to ascertain if AVDs improve clinical outcomes. The developing body of evidence suggests that AVDs may be a clinically effective therapy to reduce symptoms, but more importantly to prevent end‐organ damage and improve clinical outcomes for specific patients with AHF. The results of ongoing trials will provide more clarity on the role of AVDs in the treatment of AHF.